Romantic nationalism in Eastern Europe : Russian, Polish, and Ukrainian political imaginations - Bilenʹkyĭ, Serhiĭ (Stanford studies on Central and Eastern Europe., 2012)
An exploration of the political imagination of Eastern Europe in the 1830s and 1840s, when Polish, Russian, and Ukrainian intellectuals came to identify themselves as belonging to communities known as nations or nationalities. The author approaches this topic from a transnational perspective, revealing the ways in which modern Russian, Polish, and Ukrainian nationalities were formed and refashioned through the challenges they presented to one another, both as neighbouring communities and as minorities within a given community.